Benefitting from Synergistic Effect of Anion and Cation in Antimony Acetate for Stable CH3NH3PbI3‐Based Perovskite Solar Cell with Efficiency Beyond 21%. Issue 46 (5th October 2021) - Liu, Pengyun; Chen, Yonghui; Xiang, Huimin; Yang, Xiaoqing; Wang, Wei; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract: Both the film quality and the electronic properties of halide perovskites have significant influences on the photovoltaic performance of perovskite solar cells (PSCs) because both of them are closely related to the charge carrier transportation, separation, and recombination processes in PSCs. In this work, an additive engineering strategy using antimony acetate (Sb(Ac)3 ) is employed to enhance the photovoltaic performance of methylammonium lead iodide (MAPbI3 )‐based PSCs by improving the film quality and optimizing the photoelectronic properties of halide perovskites. It is found that Ac − and Sb 3+ of Sb(Ac)3 play different roles and their synergistic effect contributed to the eventual excellent photovoltaic performance of MAPbI3 ‐based PSCs with a power conversion efficiency of above 21%. The Ac − anions act as a crystal growth controller and are more involved in the improvement of perovskite film morphology. By comparison, Sb 3+ cations are more involved in the optimization of the electronic structure of perovskites to tailor the energy levels of the perovskite film. Furthermore, with the assistance of Sb(Ac)3, MAPbI3 ‐based PSCs deliver much improved moisture, air, and thermal stability. This work can provide scientific insights on the additive engineering for improving the efficiency and long‐term stability of MAPbI3 ‐based PSCs, facilitating the further development of perovskite‐based optoelectronics. Abstract : Benefitting from the synergistic effect of anion and cation, additive engineering employing antimony acetate enables the fabrication of stable CH3 NH3 PbI3 ‐based perovskite solar cell with efficiency beyond 21%, in which the acetate ion plays an important role in optimizing the perovskite film morphology while the antimony ion is more involved in tailoring the electronic properties of perovskite.